Creating and testing a GCP game in an asynchronous course environment: The game and future plans. Issue 1 (29th February 2020) - Jones, Carolynn T.; Jester, Penelope; Croker, Jennifer A.; Fritter, Jessica; Roche, Cathy; Wallace, Brian; Westfall, Andrew O.; Redden, David T.; Willig, James
Abstract: Introduction: The National Institute of Health has mandated good clinical practice (GCP) training for all clinical research investigators and professionals. We developed a GCP game using the Kaizen-Education platform. The GCP Kaizen game was designed to help clinical research professionals immerse themselves into applying International Conference on Harmonization GCP (R2) guidelines in the clinical research setting through case-based questions. Methods: Students were invited to participate in the GCP Kaizen game as part of their 100% online academic Masters during the Spring 2019 semester. The structure of the game consisted of 75 original multiple choice and 25 repeated questions stemming from fictitious vignettes that were distributed across 10 weeks. Each question presented a teachable rationale after the answers were submitted. At the end of the game, a satisfaction survey was issued to collect player satisfaction data on the game platform, content, experience as well as perceptions of GCP learning and future GCP concept application. Results: There were 71 total players who participated and answered at least one question. Of those, 53 (75%) answered all 100 questions. The game had a high Cronbach's alpha, and item analyses provided information on question quality, thus assisting us in future quality edits before re-testing and wider dissemination. Conclusions: The GCP Kaizen game provides an alternative method for mandated GCP training using principles of gamification. It proved to be a reliable and an effective educational method with high player satisfaction.